Surface-bulk coupling in a Bi2Te3 nanoplate grown by van der Waals epitaxy. Issue 7 (8th February 2022) - Li, Xiaobo; Meng, Mengmeng; Huang, Shaoyun; Tan, Congwei; Zhang, Congcong; Peng, Hailin; Xu, H. Q.
Abstract : Low-field magnetotransport measurements are carried out for a 3D topological insulator nanoplate at low temperatures and it is shown that taking surface-bulk state coupling into account is essential for analysis of the quantum transport measurements of the system. Abstract : We report an experimental study of the effect of coherent surface-bulk electron scattering on quantum transport in a three-dimensional topological insulator Bi2 Te3 nanoplate. The nanoplate is grown via van der Waals epitaxy on a mica substrate and a top-gated Hall-bar device is fabricated from the nanoplate directly on the growth substrate. Top-gate voltage dependent measurements of the sheet resistance of the device reveal that the transport carriers in the nanoplate are of n-type and that, with decreasing top gate voltage, the carrier density in the nanoplate is decreased. However, the mobility is increased with decreasing top-gate voltage. This mobility increase with decreasing carrier density in the nanoplate is demonstrated to arise from a decrease in bulk-to-surface electron scattering rate. Low-field magnetotransport measurements are performed at low temperatures. The measured magnetoconductivity of the nanoplate shows typical weak anti-localization (WAL) characteristics. We analyze the measurements by taking surface-bulk inter-channel electron scattering into account and extract dephasing times τ φ, diffusion coefficients D of electrons at the top surface and in the bulk, and the surface-bulk scattering times τ SB as a function of top-gate voltage and temperature. It is found that the dephasing in the nanoplate arises dominantly from electron–electron scattering with small energy transfers. It is also found that the ratio of τ φ / τ SB (a measure of the surface-bulk electron coherent coupling) is decreased with decreasing gate voltage or increasing temperature. We demonstrate that taking the surface-bulk coherent electron scattering in our Bi2 Te3 nanoplate into account is essential to understand quantum transport measurements at low temperatures.